2022
DOI: 10.3389/fcell.2022.816558
|View full text |Cite
|
Sign up to set email alerts
|

The Putative Bromodomain Protein PfBDP7 of the Human Malaria Parasite Plasmodium Falciparum Cooperates With PfBDP1 in the Silencing of Variant Surface Antigen Expression

Abstract: Epigenetic regulation is a critical mechanism in controlling virulence, differentiation, and survival of the human malaria parasite Plasmodium (P.) falciparum. Bromodomain proteins contribute to this process by binding to acetylated lysine residues of histones and thereby targeting the gene regulatory machinery to gene promoters. A protein complex containing the P. falciparum bromodomain proteins (PfBDP) 1 and PfBDP2 (BDP1/BDP2 core complex) was previously shown to play an essential role for the correct transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 78 publications
(123 reference statements)
0
23
0
Order By: Relevance
“…Our study establishes an additional activity of the PfBDP1-BRD in recognizing histone H4 and H2B.Z acetylation marks, whose functional significance with respect to the regulation of gene expression in P. falciparum has yet to be explored. The PfBDP1 protein has also been shown to form a multi-subunit complex with PfBDP2 and/or PfBDP7 [24, 27, 43]. In addition to the C-terminal bromodomain, the full-length PfBDP1 protein contains 7 ankyrin repeats located near the N-terminus, which may function as a protein-protein interaction domain.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study establishes an additional activity of the PfBDP1-BRD in recognizing histone H4 and H2B.Z acetylation marks, whose functional significance with respect to the regulation of gene expression in P. falciparum has yet to be explored. The PfBDP1 protein has also been shown to form a multi-subunit complex with PfBDP2 and/or PfBDP7 [24, 27, 43]. In addition to the C-terminal bromodomain, the full-length PfBDP1 protein contains 7 ankyrin repeats located near the N-terminus, which may function as a protein-protein interaction domain.…”
Section: Discussionmentioning
confidence: 99%
“…The P. falciparum genome also encodes for ten bromodomain-containing proteins namely, Bromodomain Proteins 1-7 (PfBDP1, PfBDP2, PfBDP3, PfBDP4, PfBDP5, PfBDP6, PfBDP7, PfBDP8, GCN5 (histone acetyltransferase GCN5), and SET1 (SET domain protein 1)), which likely recognize acetylated lysine modifications. Recent studies on PfBDP1 have shown that it is a multi-domain protein with a predicted ankyrin repeat in the N-terminal region, and a bromodomain (BRD) near the C-terminus [16,24,[27][28][29]. PfBDP1 is thought to play an important role in the activation of invasion-related genes in the asexual stage as its knockdown drastically affects the replication of P. falciparum in red blood cells.…”
Section: Bromodomain-containing Proteins Have Also Been Identified In...mentioning
confidence: 99%
See 3 more Smart Citations